Abordajes quirúrgicos en ovariohisterectomía (OVH) en gatas por celiotomia y por el flanco. - Arriciaga Macías, Anabel Esmeralda (2022)
The use of various techniques to perform Ovariohysterectomy (OVH) for sterilization currently generates many controversies, among the most common are the celiotomy technique (incision in the abdominal cavity) and the lateral technique through the right flank. In order to practice these OVH procedures, a clinical and physical examination of the patient must first be carried out, since each approach will depend on the conditions and parameters present in the animal. In these surgical procedures there will be risks and complications and they are classified from higher to lower, depending on the level of severity, when the life of the animal is compromised we will categorize it in a major complication and this happens when there is a hemorrhage due to accidental rupture of any vein, artery or blood capillary at the time of surgery and minor complications when the life of the animal is not at risk and surgical corrections are not necessary in the procedure. In veterinary clinics, the most routinely performed surgical procedure is OVH, since it is a safe alternative to prevent reproduction in cats as well as the spread of venereal diseases and the control of pathologies of reproductive origin. Currently there is not enough scientific evidence to guarantee which technique is superior to the other. However, each veterinarian must evaluate the advantages and disadvantages when choosing one of the two techniques (lateral flank and celiotomy) for OVH in cats.